2022
DOI: 10.1155/2022/9287737
|View full text |Cite
|
Sign up to set email alerts
|

Exercise Intervention Improves Blood Glucose Levels and Adverse Pregnancy Outcomes in GDM Patients: A Meta-Analysis

Abstract: Objective. The objective of this study is to systematically evaluate the effect of exercise on gestational diabetes (GDM). Methods. The databases of PubMed, Cochrane Library, Web of Science, Embase, CNKI, VIP, and Wanfang were searched to collect publications regarding physical exercises and GDM. The two researchers screened the literature, extracted the data, and analyzed the risk of bias of the included data using RevMan 5.3 software. The primary outcomes analyzed included the fasting blood glucose, 2-h post… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…The evidence supporting the benefits of PA among women with GDM is mounting. A further metanalysis published in 2022; concluded exercise intervention can improve the blood glucose parameters and can also reduce adverse pregnancy outcomes, such as premature birth and macrosomia [ 36 ]. This supports separate analyses that found requirements of insulin therapy, dosage and latency to administration were improved in the exercise intervention groups [ 8 , 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…The evidence supporting the benefits of PA among women with GDM is mounting. A further metanalysis published in 2022; concluded exercise intervention can improve the blood glucose parameters and can also reduce adverse pregnancy outcomes, such as premature birth and macrosomia [ 36 ]. This supports separate analyses that found requirements of insulin therapy, dosage and latency to administration were improved in the exercise intervention groups [ 8 , 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…Improving glucose management in pregnant women with GDM is fundamental to reduce their risk for developing pregnancy complications. For example, the recent metanalysis by Li X et al [ 45 ] shows that exercise intervention improves glucose management and reduces adverse pregnancy outcomes such as premature birth and macrosomia. Similar improvements were observed under the treatment with insulin or metformin [ 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…[25] A meta-analysis by Li et al showed that exercise prescription for GDM patients could manage GDM and improve adverse pregnancy outcomes effectively. [26] Pregnant women with GDM are recommended to exercise at least twice a week for at least 20 to 50 minutes with at least moderate intensity. [27] However, there are some limitations to be issued in this study.…”
Section: Ormentioning
confidence: 99%